Engenharia de tráfego aplicado à simulação de uma rede backbone de um provedor de internet regional utilizando o protocolo MPLS TE - OLIVEIRA JUNIOR, Cláudio Elzio Paixão de (2022)
Traffic rates on current internet providers have increased considerably due to the increasing presence of fiber optic links. With this scenario, the current challenges for ISPs (Internet Service Providers) are no longer related to transmission speed, but to guarantee quality of service (QoS - Quality of Service) for applications that require more criteria in transmission. data, such as lower delay, jitter, packet loss, among others. This work aims to implement, through the EVE- NG simulation software, a network based on a backbone topology of a provider in the city of